Allo Spedale del Bigallo. Dall’orto alla cucina, dall’accoglienza al paesaggio, dalle “camere con vista” ai percorsi esperienziali, verso un nuovo modello ospitale per il Contado Fiorentino - Micarelli, Rita (Ri-Vista. Research for landscape architecture, 2015)
This article tells the story of a monument and a landscape, the adventures lived by both and their repeated re-discoveries by a group of people delegated for their restoration. After deep surveys and participated meetings, after many periods of works and long staying in that place, that group decided that it wasn’t satisfactory to restore the monument, but it was needed to make it live again, in our contemporaneous time, as it was a living being. Moreover, this article proposes a suggestion: the “farm-hotel”, an innovative instrument to promote sustainable tourism, starting from the historical country to the cities.